(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2011)
The ability to achieve close control of porosity and pore size is the main reason that filters are produced by powder metallurgy. This study was performed using bronze alloy powder (Cu-7.5%Sn- 0.1%Fe-0.3%Pb-0.15%Zn). The samples were prepared by two methods :(1) cold die compacting at different particle size, compacting pressure, sintering time, and sintering temperature, and (2) loose powder sintering. The compacts were sintered under controlled atmosphere. After surface preparation of the samples, the microstructure was used to compute the apparent porosity. It was found that the(Loose Powder Sintering) method is optimum method to produce highly porous materials with ( 59%) porosity when selecting the proper conditions. The porosities obtained using cold die compaction are ranging between (5-41%) and sintered density ranging between (58.6-94.3%) of the theoretical mean density of the starting materials.